(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Getting infected with coronavirus in the Republic of Uzbekistan when a retrospective epidemiological analysis was conducted, it was found that the rate of infection with coronavirus in the republic has increased sharply, When we analyzed the distribution of coronavirus infection by regions, it was found that the infection was spread unevenly, the highest rate was observed in Tashkent city, the rate of infection was 28,822.1 per 100,000 inhabitants.